2019
DOI: 10.1113/jp274893
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia: a gestational cardiorenal syndrome

Abstract: It is generally accepted today that there are two different types of preeclampsia: an early‐onset or placental type and a late‐onset or maternal type. In the latent phase, the first one presents with a low output/high resistance circulation eventually leading in the late second or early third trimester to an intense and acutely aggravating systemic disorder with an important impact on maternal and neonatal mortality and morbidity; the other type presents initially as a high volume/low resistance circulation, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 239 publications
(411 reference statements)
0
26
0
1
Order By: Relevance
“…2 (4) Similarly, risk factors for cardiovascular disease predispose to the development of preeclampsia. 3 (5) In formerly preeclamptic women, the recurrence rate of preeclampsia is increased when left ventricular and diastolic dysfunction is present before conception. 4 (6) Pregnant women with prepregnancy cardiovascular disease (essential hypertension, congenital heart disease) are more likely to experience preeclampsia.…”
Section: To the Editorsmentioning
confidence: 99%
“…2 (4) Similarly, risk factors for cardiovascular disease predispose to the development of preeclampsia. 3 (5) In formerly preeclamptic women, the recurrence rate of preeclampsia is increased when left ventricular and diastolic dysfunction is present before conception. 4 (6) Pregnant women with prepregnancy cardiovascular disease (essential hypertension, congenital heart disease) are more likely to experience preeclampsia.…”
Section: To the Editorsmentioning
confidence: 99%
“…1 However, recent work into cardiovascular maladaptation of the pregnancy-induced expansion of body water volume has gained interest as a novel explanation of the hemodynamic mechanisms behind early-onset and late-onset PE. 2 Specifically, increasing evidence supports the critical role of diastolic cardiac dysfunction and venous congestion in PE-related organ dysfunction. 2 Venous congestion is a well-known phenomenon during intra-abdominal hypertension (IAH) triggering arterial hypertension, hypoperfusion, and multiple organ dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…2 Specifically, increasing evidence supports the critical role of diastolic cardiac dysfunction and venous congestion in PE-related organ dysfunction. 2 Venous congestion is a well-known phenomenon during intra-abdominal hypertension (IAH) triggering arterial hypertension, hypoperfusion, and multiple organ dysfunctions. 3 Interestingly, PE is associated with increased intra-abdominal pressure (IAP), irrespective of gestational age or birthweight, and correlates with maternal intestinal permeability and oliguria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these two pregnancy-related disorders have been widely studied, their cause remains unknown. Pathophysiological mechanisms involve the reduction of maternal placental blood flow as of week 20 of gestation, with an increase in peripheral vascular resistance that predominantly takes place in the kidney, liver, and brain [4][5][6][7][8][9]. It has been reported that placenta plays a key role in the pathogenesis of preeclampsia, and it was assumed that, after delivery, its influence in the maternal cardiovascular system would be over.…”
Section: Introductionmentioning
confidence: 99%